Empowering Rural Teachers Through Digital Literacy Training: A Community Service Initiative to Bridge the Technological Gap in Elementary Schools - Wajnah Wajnah; Bahmid Hasbullah; Dina Mayadiana Suwarma; Idris Moh. Latar; Yasriuddin Yasriuddin (International Journal of Community Service (IJCS), 2026)
The persistent urban–rural digital divide in Indonesia severely limits the quality of technology-enhanced learning in elementary schools. This study evaluates a community service initiative that provided a structured digital literacy training programme to 60 rural elementary teachers in West Java. Employing a one-group pretest–posttest quantitative design, the investigation measured teachers’ digital literacy competence before and after a five-day intensive workshop followed by four weeks of online mentoring, using a validated 30-item Digital Literacy Competence Scale grounded in the DigCompEdu framework. Data were analyzed through descriptive statistics, paired-samples t‑test, Cohen’s d effect size, and hierarchical multiple regression. The results demonstrate a substantial and statistically significant improvement in overall digital literacy, with a very large effect size (d = 2.39). All six digital competence sub-domains increased significantly, although content creation displayed the smallest gain. Hierarchical regression revealed that pretest scores, younger age, and prior ICT training were significant positive predictors of post-training competence, whereas years of teaching experience and school infrastructure were not. Perceived barriers such as unreliable internet connectivity and device scarcity remained high despite the intervention. The findings confirm that intensive, community-based digital literacy training can dramatically enhance rural teachers’ digital competence, yet they also highlight the necessity of addressing systemic infrastructure gaps. Implications for teacher professional development policy and community service design are discussed, together with study limitations and directions for future research